Patients skin dose measurements during interventional radiological examinations using Gafchromic XR-RV3 FILM - Svetlana S. Sarycheva (Радиационная гигиена)
This work is devoted to the assessment of the absorbed dose in the skin of patients undergoing interventional radiological examinations. There is a probability of deterministic effects in the skin of patients due to high doses of radiation during this type of medical examinations. The aim of this work was to conduct direct measurements of the absorbed dose in the skin of patients undergoing interventional radiological procedures using special dosimetric radiochromic films Gafchromic XR-RV3 to visualize the distribution of radiation over the patient’s skin surface and to study the possibility of exceeding the threshold values for the deterministic effects in the skin. The paper discusses the features of measurements with GafchromiC XR-RV3 films. The method of film digitization on conventional flatbed scanner and image processing with the ImageJ program was tested. The obtained calibration curve for this type of film was presented. The skin dose distributions for several interventional studies obtained with radiochromic films were presented. The measured value of the maximum absorbed dose in the skin for four of the fourteen analyzed procedures exceeded the threshold value of the absorbed dose for the occurrence of skin erythema in 2 Gy. The highest values of the maximum absorbed dose in the skin were obtained for the coronary angioplasty – 3.2 Gy and for the procedure of embolization of the uterine arteries – 2.9 Gy.